(untitled) (Dhaka University Journal of Business Studies, 2021)
COVID-19 has posed a significant threat to the global education system. Rethinking alternative classes for continuing education is the central issue for coping with the new-normal system. The study aims to seek the preparedness and practicality of online education in developing countries from Bangladesh’s perspective. The study examined primary data collected through a survey. In line with the descriptive analysis of the collected data, a logistic regression model has been applied to justify the hypotheses. Among sixteen variables, we have found seven variables that significantly impact the students’ opinion regarding conducting classes in online. The findings show a positive association of lack of high internet speed, frequent disconnection issues during class time, mental stress about COVID-19, lack of engaging course contents, and deteriorating family financial condition with students’ unwillingness towards online class during COVID-19.The study also revealed that students who have technical expertise in online classes are more interested in this type of class format. In this changing circumstance, online class format is an alternative channel to maintain the continuity in higher studies in Bangladesh. Thus the educational institutions can arrange training programs for teachers to improve the course contents. The institutions can also support the students by providing financial assistance for purchasing devices, internet data packages, guidelines for joining in online class and consulting to relieve mental stress. The government can also play a significant role by ensuring nationwide high-speed internet service and subsidy to purchase internet data for the students. Journal of Business Studies, Vol. XLII, No. 1, April 2021 Page 133-150